Yeast transformation stress, together with loss of Pah1, phosphatidic acid phosphatase, leads to Ty1 retrotransposon insertion into the INO4 gene. Issue 3 (10th February 2020) - Kudo, Shinnosuke; Shiino, Hiroya; Furuta, Shiina; Tamura, Yasushi
Abstract: Most phospholipids are synthesized via modification reactions of a simple phospholipid phosphatidic acid (PA). PA and its modified phospholipids travel between organelle membranes, for example, the endoplasmic reticulum (ER) and mitochondrial inner membrane, to be converted to the other phospholipids. To gain insight into mechanisms of the phospholipid biosynthetic pathways, we searched for factors whose loss affects the phospholipid synthesis using an in vitro phospholipid transport assay. Among the various factors that were tested, we noticed that a lack of Pah1, which is a phosphatidic acid phosphatase, led to severe defects in phospholipid synthesis, which was not rescued by re‐expression of wild‐type Pah1. These results indicated other mutations in addition to the deletion of Pah1. Interestingly, we found that stress conditions associated with the yeast transformation process triggered a disruption of the INO4 gene by insertion of the Ty1 retrotransposon in pah1 ∆ strains. Additionally, we noticed that loss of the diacylglycerol kinase Dgk1, which has an opposing function to Pah1, suppressed the insertional mutation of INO4 . These findings suggest that normal Pah1 function is critical for the suppression of insertional mutations by retrotransposon elements.